INNOVATION MANAGEMENT FROM DYNAMIC CAPABILITY MANAGEMENT LENSE IN SCHOOL SETTINGS: A CONCEPTUAL FRAMEWORK - Johan .; Poltak Sinaga; Rudy Pramono; Niko Sudibjo (Jurnal Education and Development, 2021)
Implementation of innovation is the main indicator of success for innovation initiatives. The challenge on dynamic capability management, particularly for innovation, has been in place and studied by scholars. Yet, research regarding this matter from a strategic level and from school leaders’ perspective is limited. Interviews conducted to school leaders in Indonesia showcase four resources to be managed for innovation in schools: human resources, technology, communication, and budget; each with their own antecedents. The focus to ensure success falls into human resources, namely willingness to adopt, understanding of the concept of teacher, comprehension level and learning speed. Meanwhile, from a technology standpoint, these antecedents include fulfillment of users’ needs, integration with applied technologies, budget fitness and hardware requirements. Communication resources and their dynamics are text and visual based communication, meeting, and surveys. Meanwhile, the dynamics surrounding the budget are fitness with purpose and school’s plan, return on investment, and external contribution. This study supports the creation of a new proposition on innovation dynamic capability management from the school's perspective. School leaders can use this research as a reference point to strategize future innovation projects.